DESIGN AND SIMULATION OF THE MANUFACTURING PROCESS PLAY HINO TRUCK VEHICLE SHAFT USING THE MASTERCAM X5 TO GENERATE G-CODE - Aa Santosa; Dhimas Aditia (Jurnal Mekanika dan Manufaktur, 2023)
In its development, every manufacturing industry increasingly makes people think more creatively and are faced with new problems, especially in making new innovations. The purpose of these production issues is to achieve faster and more efficient production targets. The metal machining process is an important factor to support the quality of the final product, but there is one obstacle that must be faced.The main shaft is a component on hino truck vehicles, to produce components that are precise in terms of size and good surfaces are used for machining processes using a CNC machine, to simplify the manufacturing process, it is assisted by the Cam X5 master program to produce the G Code program to be used on the machine CNC. The manufacturing process uses a CNC Turning Machine.This research is an application of the CAD CAM course, the mastercam software application is very helpful in component manufacturing innovation. The main shaft is a form of a product resulting from the machining process, the material for the main shaft is made of AISI 1050 material